A subexponential-time algorithm for the Maximum Independent Set Problem in Pt-free graphs - Brause, Christoph (Discrete Applied Mathematics, 2017)
The Maximum Independent Set Problem is known to be NP-hard in general. In the last decades lots of effort were spent to find polynomial-time algorithms for Pt-free graphs. A recent result presents such an algorithm for P5-free graphs. On the other hand, the complexity status for larger t is still unknown. In this paper we present a subexponential algorithm for the Maximum (Weighted) Independent Set Problem in Pt-free graphs.